2012
DOI: 10.1093/brain/aws267
|View full text |Cite
|
Sign up to set email alerts
|

Functional neurological recovery after spinal cord injury is impaired in patients with infections

Abstract: Infections are a common threat to patients after spinal cord injury. Furthermore, infections might propagate neuronal death, and consequently contribute to the restriction of neurological recovery. We investigated the association of infections (i.e. pneumonia and/or postoperative wound infections) with functional neurological outcome after acute severe traumatic spinal cord injury. We screened data sets of 24 762 patients enrolled in a prospective cohort study (National Spinal Cord Injury Database, Birmingham,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
101
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(111 citation statements)
references
References 41 publications
5
101
0
2
Order By: Relevance
“…Color image is available online at www.liebertpub.com/neu after SCI. [60][61][62][63][64] Interestingly, at the peak of pronounced immune compromise (2 weeks after injury), we also observed enhanced autoreactive splenic activation. Indeed, this ''paradox'' of coexisting immune suppression and autoimmunity is a common concept in systemic autoimmune diseases, 65 and is now recognized as part of SCI pathology.…”
Section: Discussionsupporting
confidence: 52%
“…Color image is available online at www.liebertpub.com/neu after SCI. [60][61][62][63][64] Interestingly, at the peak of pronounced immune compromise (2 weeks after injury), we also observed enhanced autoreactive splenic activation. Indeed, this ''paradox'' of coexisting immune suppression and autoimmunity is a common concept in systemic autoimmune diseases, 65 and is now recognized as part of SCI pathology.…”
Section: Discussionsupporting
confidence: 52%
“…However, subacute phases after SCI may be amenable to delayed protective interventions that target and control peripheral infections and other peripheral sources of circulating inflammatory stimuli. Epidemiological studies show that comorbid infections such as pneumonia worsen functional outcome after human SCI (128)(129)(130). Potential cellular mechanisms may involve prolonged inflammation at the lesion site that results in increased tissue damage.…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 99%
“…3 In addition to increased morbidity and mortality, infections after SCI may affect neurologic recovery. 2,3 A recent study found that infections impaired the return of muscle strength up to 1 year postinjury; however, the long-term consequences remain uncertain. 2 The aim of this study was to investigate whether infections occurring in an acute care setting after SCI affected long-term functional recovery and survival.…”
mentioning
confidence: 99%
“…The NSCID prospectively gathers data from 25 specialized traumatic SCI care centers. 2 Inclusion criteria were admission within 24 hours after injury between 1995 and 2005, age between 17 and 75, a cervical SCI, complete baseline and infection data, and an American Spinal Cord Injury Association Impairment Scale (AIS) grade of A, B, or C (see table e-1 at Neurology.org for a full description of the AIS grading system). Participants were excluded if they resided in a hospital or nursing home prior to injury, had serious concomitant injuries affecting consciousness, or were rehospitalized for unspecified infectious or parasitic diseases during the follow-up period.…”
mentioning
confidence: 99%